“In vitro” Neutralization with Oxalate Ion of the Anticoagulant Effect of Heparin - Cruz, W. O; Meis, L; Dietrich, C. P (Thrombosis and Haemostasis, 1961)
Heparinized blood or plasma coagulates if, after addition of oxalate, recalcification follows. Of the decalcifying agents only oxalate ion has been suitable for demonstrating this phenomenon. Oxalate seem to accomplish two different roles connected with this effect: a fundamental one, i. e., to sensitize a heparinlipoprotein complex to the action of an anti-heparin factor found in normal plasma or serum and a secondary one, related to its capacity to adsorb this antiheparin factor. The latter is removable by centrifugation. This anti-heparin oxalate factor, which is able to counteract the action of heparin after previous addition of oxalate, was found in sequestrened, Dowex 50 resin plasma or in serum, but is not active in citrated plasma. This factor was removed from plasma by adsorption with barium sulfate, aluminium hydroxide or calcium oxalate and was eluted from these adsorbants after incubation with saline.